Perbandingan Karakteristik Kimia Trypsin Inhbibitor Biji dan Kecambah Kedelai - Bayu Kanetro; Zuheid Noor; Sutardi Sutardi; Retno Indrati (agriTECH, 2006)
This study investigated the changes in trypsin inhibitor (TI) activity, amino acid composition and protein patterns after 36 hours germination of soybeans. TI was extracted by a combination of pH precipitation and centrifugation. TI activity of seeds and germinated soybean were 1.64 and 1.68 IU/mg seeds (db) respectively. Heating of crude TI decreased heat stability of TI. The decrease of TI activity of germinated soybeans due to heating was lower than seeds. The amino acid composition and protein patterns of soybeans changed after 36 hours germination. Thr, Ala, Trp, Met and Lys decreased significantly, while Asp, Glu, Val, Phe, and Ile  increased significantly. The SDS-PAGE analysis showed that the seeds contain high-molecular weight of proteins which were degraded after 36 hours germination result in smaller molecular weight of proteins.